Clinical instructors' perception of a faculty development programme promoting postgraduate year-1 (PGY1) residents' ACGME six core competencies: a 2-year study. Issue 2 (24th November 2011) - Lee, Fa-Yauh; Yang, Ying-Ying; Hsu, Hui-Chi; Chuang, Chiao-Lin; Lee, Wei-Shin; Chang, Ching-Chih; Huang, Chia-Chang; Chen, Jaw-Wen; Cheng, Hao-Min; Jap, Tjin-Shing
Abstract : Objective: The six core competencies designated by Accreditation Council for Graduate Medical Education (ACGME) are essential for establishing a patient centre holistic medical system. The authors developed a faculty programme to promote the postgraduate year 1 (PGY1 ) resident, ACGME six core competencies. The study aims to assess the clinical instructors' perception, attitudes and subjective impression towards the various sessions of the 'faculty development programme for teaching ACGME competencies.' Methods: During 2009 and 2010, 134 clinical instructors participated in the programme to establish their ability to teach and assess PGY1 residents about ACGME competencies. Results: The participants in the faculty development programme reported that the skills most often used while teaching were learnt during circuit and itinerant bedside, physical examination teaching, mini-clinical evaluation exercise (mini-CEX) evaluation demonstration, training workshop and videotapes of 'how to teach ACGME competencies.' Participants reported that circuit bedside teaching and mini-CEX evaluation demonstrations helped them in the interpersonal and communication skills domain, and that the itinerant teaching demonstrations helped them in the professionalism domain, while physical examination teaching and mini-CEX evaluation demonstrations helped them in the patients' care domain. Both the training workshop and videotape session increase familiarity with teaching and assessing skills. Participants who applied the skills learnt from the faculty development programme the most in their teaching and assessment came from internal medicine departments, were young attending physician and had experience as PGY1 clinical instructors. Conclusions: According to the clinical instructors' response, our faculty development programme effectively increased their familiarity with various teaching and assessment skills needed to teach PGY1 residents and ACGME competencies, and these clinical instructors also then subsequently apply these skills.